(3SdSdI GdNhGLcGf aj BOGH YHhOjI GdCYjGf aj WQjbI SGOGJ GdfbTHfOjIs - (3CMeO GdWQHRhfj,J (B1195 (3g` s
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje GdMeO ddg GdPi TQM HGdCPcGQ NaGjG dWGFa UOhQ GdPGcQjf CeG HYO aEf CaVd GdC(B'(3eGd hCTQa GdCMhGd EJHGY GdSfI ai cd MGd s
(3BNQgG (B:s
(3bGd GdTjN CHh MaU bOS Gddg SQg MQSJ bdHi YTQjf djdI Ke MQSfi bdHi YTQjf SfI Ke hQOJ MGdg aUQfG ajgG eMQhSjf LejYkG Udi Gddg Ydi SjOfG hehdGfG eMeO hYdi Bdg hUMHg CLeYjf hGdPjf GJHYhge HEMSGH Edi jhe GdOjf hGdMeO ddg QH GdYGdejf Je s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3cJHJ HYV GdcdeGJ HGdMeQIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B256s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B2 - (3U (B21s
Keywords: (3GdJUha hGdBOGH GdTQYjIs